Pengaruh Model Pembelajaran POE (Predict-Observ-Explain) terhadap Hasil Belajar dan Kreativitas Fisika Peserta Didik - Nora Paoliana; Muhammad Taufik; Joni Rokhmat (Mataram University, 2020)
This study aims to determine the effect of POE (Predict-Observe-Explain) learning model on student’s learning outcomes and creativity of physics. This type of research was quasi-experiment and used nonequivalent control group design. The population in this study were all students of class XI MIPA in SMA 1 Narmada academic year 2018/2019. Samples were taken using purposive sampling technique and class XI MIPA 3 as the experimental class and class XI MIPA 5 as the control class. Learning outcomes data were obtained using multiple choice tests, while creativity data were obtained using essay tests. The research hypothesis was tested using the N-gain test to analyze the increase in learning outcomes and creativity of students per indicator and MANOVA test to test the effect of the application of POE (Predict-Observe-Explain) learning model on student’s learning outcomes and creativity of physics using IBM SPSS 23 software. The results of hypothesis test indicate that 1) N-gain test, improvement in learning outcomes and creativity were included in the medium category 2) MANOVA test, there was an effect of POE (Predict-Observe-Explain) learning model on student’s learning outcomes and creativity of physics. Keywords: POE (Predict-Observe-Explain) learning model; learning outcomes; creativity